Drama w rozwijaniu kompetencji społecznych i emocjonalnych dzieci w wieku wczesnoszkolnym - Gałązka, Alicja (Chowanna, 2019)
The article presents the problem of using drama in the development of social and emotional competences of children in early school age. In preschool and early school age children undergo many dynamic developmental changes, especially in the area of social, emotional, cognitive and communication development. All these changes help children better understand and organize the world around them and think about it in a creative and increasingly independent and complex way. Children develop their metacognitive abilities, they better understand their own emotions and behavior, and at the same time, assimilate the norms and principles of social life. In the article, the author points to the possibility of using drama to support emotional and social development of a child. Drama, thanks to the fact that it oscillates between fiction and reality, gives the possibility of safe exploration of various social and moral attitudes and expression of emotions. The article is a kind of summary of the most important notions and dimensions of the use of drama in work with children of early school age in the last two decades.